2023
DOI: 10.1038/s41598-023-27517-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural and neurobiochemical differences in brains from high-performance and native hen breeds

Abstract: Selection of livestock has not only led to changes in the level of their performance but also modified their behavior. As a result, within a single species, we have to deal with different behaviors of different breeds. In our study, we assumed that the different behaviors within a species are due to differences in the morphology and physiology of behavior-related systems. Two breeds of hens were used as a model: the highly reactive, fearful and high-performance Leghorn breed and proactive, unselected Green-leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
1
1
Order By: Relevance
“…One previous study found DA turnover to be significantly reduced in the hippocampus and attributed this to fast uptake by dopamine transporters [18,74]. Lower dopamine turnover along with increased CORT may also represent higher stress levels [68], which is the opposite of what we observed in DA turnover levels in the hypothalamus of SYN birds.…”
Section: Dopaminecontrasting
confidence: 93%
See 1 more Smart Citation
“…One previous study found DA turnover to be significantly reduced in the hippocampus and attributed this to fast uptake by dopamine transporters [18,74]. Lower dopamine turnover along with increased CORT may also represent higher stress levels [68], which is the opposite of what we observed in DA turnover levels in the hypothalamus of SYN birds.…”
Section: Dopaminecontrasting
confidence: 93%
“…Dopamine has also been shown to assist with memory formation in humans [67]. Dopamine levels can also reflect the welfare status of laying hens, as it can improve the animal's ability to cope with fear and stress [68,69]. In addition, it has been observed in rats that elevated DOPAC levels may be associated with a stressful environment [70].…”
Section: Dopaminementioning
confidence: 99%